„Czemuż nie zostawiłem tej kartki pustej?!” – obraz felietonopisarstwa i felietonisty w tekstach Macieja Stuhra pisanych dla „Zwierciadła” - Rybka, Małgorzata; Wrześniewska-Pietrzak, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The text presents linguistic image of a feuilletonist and writing a feuilleton in the texts written by Maciej Stuhr in “Zwierciadło” from January 2009 to April 2016. Analyses were conveyed according to the cognitive methodology and lead to the constructing the concept of writing a feuilleton that is combined with the problem of autotematism in the texts of Maciej Stuhr. The linguistic image of a feuilletonist is presented regarding the theory of autobiographism and the sender – reader relationship. The mentioned elements have enabled the authors of this article to read the entire image of a feuilletonist and present basic types of sender – reader relationship that characterizes Maciej Stuhr as a journalist – feuilletonist that is aware of his writing workshop.